Combining metformin with lactate transport inhibitors as a treatment modality for cancer - recommendation proposal - Benjamin, Don; Hall, Michael N. (Frontiers in Oncology, 2022)
Highly glycolytic tumors excrete lactate to maintain cellular homeostasis. Inhibiting lactate export by pharmacologically targeting lactate transporters is a validated strategy to specifically target cancer cells. Work from many laboratories show that the simultaneous inhibition of lactate export and mitochondrial respiration elicits strong synthetic lethality. The mitochondrial inhibitor, metformin, has been the subject of numerous clinical trials as an anti-cancer agent. We propose that, in future clinical trials, metformin be combined with lactate transport inhibitors to exploit this synergistic interaction.